Dual loss of USP10 and p14ARF protein expression is associated with poor prognosis in patients with small intestinal adenocarcinoma - Joon Seon Song; Joo Mi Yi; Hanbyoul Cho; Chel Hun Choi; Yoonho Park; Eun Joo Chung; Jaewhan Song; Joon-Yong Chung; Seung-Mo Hong (Tumor Biology)
Oncogene-induced senescence occurs following oncogene activation in normal cells and is considered as a critical tumor-suppressing mechanism. Ubiquitin-specific protease 10 (USP10) has been reported to play a vital role in oncogene-induced senescence via the deubiquitination-dependent stabilization of p14ARF. However, knowledge of the clinical significance of USP10 and p14ARF expression in patients with small intestinal adenocarcinoma is limited. To study the clinical significance of USP10 and p14ARF expression, we performed immunohistochemistry for USP10 and p14ARF on 195 surgically resected small intestinal adenocarcinoma specimens. Furthermore, we performed methylation analysis on five small intestinal adenocarcinoma samples and matched adjacent normal intestinal tissue samples. UPS10 ( p  = 0.023) and p14ARF ( p  = 0.007) expression were significantly decreased in adenocarcinoma in comparison with normal tissue. The loss of USP10 was observed in 124/194 (63.9%) of small intestinal adenocarcinoma samples and was correlated with a higher pT stage ( p  = 0.044), lymphatic invasion ( p  = 0.033), and the absence of sporadic adenoma ( p  = 0.024) and peritumoral dysplasia ( p  = 0.019). p14ARF expression was downregulated in 75/195 (38.5%) of small intestinal adenocarcinoma samples and was associated with vascular ( p  = 0.011) and lymphatic ( p  = 0.013) invasions. The loss of USP10 expression was associated with the loss of p14ARF expression ( r  = 0.342, p  < 0.001). Multivariate survival analysis revealed that the combined loss of USP10 and p14ARF expression could be an independent prognostic factor for overall survival in small intestinal adenocarcinoma. Furthermore, the aberrant hypermethylation of the USP10 and p14ARF promoter could be a key mechanism for the downregulation of USP10 and p14ARF proteins in small intestinal adenocarcinoma. These findings suggest that the dual loss of USP10 and p14ARF could be used as a prognostic indicator of small intestinal adenocarcinoma.